Pterygium Surgery Utilizing Limbal Conjunctival Autograft and Subconjunctival Amniotic Membrane Graft in High-Risk Populations - Shusko A (Dove Medical Press, 2020)
Alexander Shusko,1 Barry A Schechter,2 John A Hovanesian3 1Nassau University Medical Center, Department of Ophthalmology, East Meadow, NY 11554, USA; 2Florida Eye Microsurgical Institute, Boynton Beach, FL 33426, USA; 3Harvard Eye Associates, Laguna Hills, CA 92653, USACorrespondence: Alexander ShuskoNassau University Medical Center, 2201 Hempstead Turnpike, East Meadow, NY 11554, USATel +1 949-246-1737Email ashusko@gmail.comObjective: To measure the outcomes of primary pterygium excision with a limbal conjunctival autograft when combined with the adjunctive use of a prophylactic subconjunctival graft of amniotic membrane to decrease the recurrence rate after surgery in an ethnically diverse population with a statistically higher risk for recurrence (African American, Asian, Caribbean, Asian, Latin).Design: This is a retrospective, non-comparative study of post-operative outcomes.Participants: A total of 355 patients, totaling 493 eyes, with clinically significant, primary pterygia.Patients and Methods: Patients were enrolled into the study based on the need for pterygium surgery and if they underwent primary pterygium excision with conjunctival autograft with subconjunctival amniotic membrane placement. Patients with recurrent pterygium or those with pseudopterygium were excluded from this study. All surgeries took place at the Florida Eye Microsurgical Institute (Boynton Beach, FL) between June 2006 and October 2013 by a single surgeon (BAS). Patients were seen on post-operative day 1, 7, 30, 90, 180 and 365 to evaluate for pterygium recurrence. Pterygium recurrence is defined in this study as growth greater than 1 mm past the corneal limbus at or after 6 months.Results: There were six cases of recurrent pterygium for a recurrence rate of 1.22% ± 0.97% (n=493, p=0.05). Follow-up ranged from 6 months to 6 years (mean 28 months).Conclusion: Primary pterygium excision with a limbal conjunctival autograft and placement of a subconjunctival amniotic membrane graft has a low recurrence rate consistent with previously published data.Keywords: pterygium, autograft, amniotic graft, technique, recurrence, cornea